2015
DOI: 10.5946/ce.2015.48.5.411
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Gallbladder Drainage for Acute Cholecystitis

Abstract: Background/AimsSurgery is the mainstay of treatment for cholecystitis. However, gallbladder stenting (GBS) has shown promise in debilitated or high-risk patients. Endoscopic transpapillary GBS and endoscopic ultrasound-guided GBS (EUS-GBS) have been proposed as safe and effective modalities for gallbladder drainage.MethodsData from patients with cholecystitis were prospectively collected from August 2004 to May 2013 from two United States academic university hospitals and analyzed retrospectively. The followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 56 publications
0
32
1
4
Order By: Relevance
“…Eighteen studies (8, 16-25, 28, 30-33, 36, 37) (8,23,29,30,(32)(33)(34)38) were rated as high quality, 10 (17, 19, 21, 24, 25, 27, 28, 31, 35, 36) were of moderate quality, and 4 (16,18,20,22) were of low quality as per the NOS quality assessment. The 2 randomized studies (26,37) had lowrisk of bias as per the Cochran tool for assessing risk of bias.…”
Section: Identification Of Studies and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen studies (8, 16-25, 28, 30-33, 36, 37) (8,23,29,30,(32)(33)(34)38) were rated as high quality, 10 (17, 19, 21, 24, 25, 27, 28, 31, 35, 36) were of moderate quality, and 4 (16,18,20,22) were of low quality as per the NOS quality assessment. The 2 randomized studies (26,37) had lowrisk of bias as per the Cochran tool for assessing risk of bias.…”
Section: Identification Of Studies and Study Characteristicsmentioning
confidence: 99%
“…Therefore a total of 66 full-text articles were reviewed, of which 23 studies (8, with 809 patients were included in the meta-analysis for primary outcomes of interest. One additional study (38) containing overlapping data with Widmer et al (33) was included in the secondary outcome of interest only. The search strategy is summarized in Figure 1.…”
Section: Identification Of Studies and Study Characteristicsmentioning
confidence: 99%
“…Recently, promising outcomes of endoscopic gallbladder drainage have been shown for ACC. 28,29 This might have a role in ACC and choledocholithiasis cases, as it could combine the drainage of the bile duct and the gallbladder in the same procedure, resulting in a decreased risk for patients. Nevertheless, there are still only a few reports in the literature about this topic, and further results from larger series are needed to define its role in the treatment of ACC.…”
Section: Discussionmentioning
confidence: 99%
“…As only 1 study on EGBD in patients receiving ATT was retrieved through the search method mentioned above, articles were additionally searched using the keywords "ETGBD" and "EUS-GBD". As a result, 27 studies on ETGBD 6,22-47 and 26 studies on EUS-GBD 8,37,40,45,46, were newly found. Finally, 28 studies on ETGBD and 26 studies on EUS-GBD were evaluated in this review, which included some cases with bleeding tendency and ATT administration.…”
Section: Study Collectionmentioning
confidence: 99%
“…Twenty-six studies 8,37,40,45,46, on EUS-GBD, including 1 RCT, 4 prospective studies, and 21 retrospective studies, were analyzed ( Table 3). The puncture sites were the duodenal bulb in 55% (334/609), the antrum in 44% (268/609), and the jejunum in 1% (7/609).…”
Section: Present Status Of Egbd: Etgbd and Eus-gbdmentioning
confidence: 99%